The Nazi persecution of Jews and the African American freedom struggle. (8th August 2019) - Webb, Clive
ABSTRACT: Webb's article assesses the impact of the Nazi persecution of European Jews on black civil rights activism in the United States. It demonstrates how African Americans, motivated by genuine moral outrage as well as political opportunism, drew explicit analogies between their own oppression and the suffering of European Jewry. Black activists decried what they saw as the hypocrisy of white Americans for condemning Nazism while complacently ignoring the often violent racial discrimination that persisted in their own country. African Americans hoped that in highlighting this contradiction they would embarrass their own government into taking more interventionist action against white supremacists and thereby advance the cause of racial equality. This strategy persisted throughout the Second World War and the mass civil rights activism of the decades that followed.